PENGARUH CITRA MEREK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HP MEREK OPPO DI SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Edi Cahyono (Jurnal Bisnis, Manajemen, dan Akuntansi, 2018)
This research aims to determine the influence of brand image, price and promotion together or partially and to know the variables that significantly influence the purchasing decision of HP OPPO in Yogyakarta. Independent variables used in this research are brand image (X1), price (X2) and promotion (X3). While the dependent variable is the purchase decision (Y). The research method used in this research is quantitative research method by using a sample of 65 respondents. Data analysis method used in this research is multiple linear regression analysis method. Data processing is done by using computer software SPSS 20.0 for Windows. Based on t test results can be seen that the promotion variable significantly influence purchasing decisions, while the brand image and price variables have no significant effect onpurchasing decisions. In addition, brand image, price and promotion contribute 42% to thepurchase decision. While the rest equal to 58% influenced by other variables not examined in thisresearch.